Study of Wireless Network Security and Interworking: Exploring the Challenges and Solutions for Secure Interworking of Wireless Networks (Journal of Advances and Scholarly Researches in Allied Education, 2011)
A variety of wireless technologies have been standardizedand commercialized, but no single technology is considered the best because ofdifferent coverage and bandwidth limitations. Thus, interworking betweenheterogeneous wireless networks is extremely important for ubiquitous and highperformance wireless communications. Security in interworking is a majorchallenge due to the vastly different security architectures used within eachnetwork. The goal of this article is two-fold. First, we provide a comprehensive discussion of securityproblems and current technologies in 3G and WLAN systems. Second, we provideintroductory discussions about the security problems in interworking, the stateof the art solutions, and open problems. IndexTerms—WirelessLAN, Land mobile radio cellular systems, Internetworking, Communication systemsecurity, Computer network security, Data security